Zonisamide as treatment option in persistent migraine aura. Issue 4 (12th April 2021) - Kaltseis, Katharina; Frank, Florian; Broessner, Gregor
Abstract : Persistent migraine aura without infarction is a rare but debilitating condition. Treatment options are mostly anecdotal and limited due to inefficacy and side effects. We present a 16-year-old female patient with triple X syndrome, having persistent aura symptoms for over 2 years, consisting of continuous visual and sensory sensations. Previous treatments with seven different migraine preventatives were not successful. The patient successfully responded to zonisamide against refractory prolonged aura and remained symptom-free under the ongoing treatment without any relevant side effects. Zonisamide may be considered a new and safe treatment option for patients with persistent migraine aura.